(untitled) (Sains Humanika, 2019)
This study aims to identify the psychological and social supports on intergenerational relationships among adult children who care for the elderly (parents) in the multi-ethnic community of Sabah. The objective of the study was to examine the influence of emotional and social support on the intergenerational relationship in the elderly care. There are 200 questionnaires that can be used from 250 respondents consisting of young adults who play the role of guardians of the elderly. Three sets of questionnaires were used in this study: the Parent-Child Interaction Questionnaire-Revised (PACHIQ-R) (Lange, 2001) questionnaire was adapted in this study is the current version of the results of the modification from the First Phase version of The Parent- Child Interaction Questionnaire (PACHIQ) (Lange, Blonk & Wiers, 1998) to measure the intergeneration relationship. Next, The Emotional Support Scale questionnaire (ESS) developed by Hisada, Seng and Minoguchi (1989) was used to measure psychological support whereas Social Support Questionnaire (SSQ) by Sarason, Levine, Basham (1983) for measuring social support. Â Regression analysis from SPSS software was used to analysis the influence between variables. Studies show that emotional support contributes to the intergenerational relationship. Social support contributes 27 percent to variance in intergenerational relationships. While the combination of two forms of social and emotional support contributes 40 percent variance to the intergenerational relationship, an increase of 13 percent. This finding shows that both forms of support can help improve intergenerational relationships between children acting as guardians with older parents. The implication of this study suggests that there is a need to develop a policy module based on the National Elderly Policy (DWEN) which needs to be done in holistic and integrated national action plans to ensure the welfare of the guardians as well as the elderly.